2020
DOI: 10.3390/s20041175
|View full text |Cite
|
Sign up to set email alerts
|

Camera Calibration with Weighted Direct Linear Transformation and Anisotropic Uncertainties of Image Control Points

Abstract: Camera calibration is a crucial step for computer vision in many applications. For example, adequate calibration is required in infrared thermography inside gas turbines for blade temperature measurements, for associating each pixel with the corresponding point on the blade 3D model. The blade has to be used as the calibration frame, but it is always only partially visible, and thus, there are few control points. We propose and test a method that exploits the anisotropic uncertainty of the control points and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…In our experimental measurements using the color sensor, we found that the highest influences on the measured values came from the illumination of the scanned object, the distance of the sensor to scanned object and whether the scanned object was moving or stopped [ 22 , 23 , 24 ]. Therefore we decided to perform measurements with different combinations of these factors.…”
Section: Resultsmentioning
confidence: 99%
“…In our experimental measurements using the color sensor, we found that the highest influences on the measured values came from the illumination of the scanned object, the distance of the sensor to scanned object and whether the scanned object was moving or stopped [ 22 , 23 , 24 ]. Therefore we decided to perform measurements with different combinations of these factors.…”
Section: Resultsmentioning
confidence: 99%
“…The motion estimation of 3D points is dealt with using perspective-n-point (PnP) [46] or iterative close point (ICP) [47]. Several approaches have been proposed to solve PnP and ICP [48], including direct linear transformation (DLT) [49] and singular value decomposition (SVD) [50].…”
Section: Vision Combined With Depth Informationmentioning
confidence: 99%
“…Currently, there are many methods proposed to solve this problem. Among these, the DLT [14,15] method is classical and efficient but vulnerable to noise interference and has poor robustness. Li et al have proposed an RPnP [16] method, which can always present stable calculation results regardless of the number of feature points, but it cannot get a unique solution when using the least square error, and its solving accuracy needs to be improved.…”
Section: Introductionmentioning
confidence: 99%